PENDIDIKAN AGAMA KRISTEN DALAM MATIUS 28:19-20 - Yosia Belo (JURNAL LUXNOS, 2019)
Abstract: This article talks about a biblical study of the text of Matthew 28: 19-20. This study was conducted to gain an understanding of Christian Religious Education in Matthew 28: 19-20. So that every PAK teacher can apply in applying and teaching students. Abstrak: Artikel ini berbicara tentang kajian biblika terhadap teks Matius 28:19-20. Kajian ini dilakukan untuk mendapatkan pemahaman tentang Pendidikan Agama Kristen dalam Matius 28:19-20. Supaya dapat diterapkan oleh setiap guru PAK dalam menerapkan dan melakukan pengajaran terhadap peserta didik.